2012
DOI: 10.1126/science.1205452
|View full text |Cite
|
Sign up to set email alerts
|

Comment on “Probing the Ultimate Limit of Fiber-Optic Strain Sensing”

Abstract: Gagliardi et al . (Reports, 19 November 2010, p. 1081) described an ultrahigh-resolution fiber-optic strain sensor. This comment addresses an error in the calculation of the fundamental thermodynamic noise in optical fiber resonators and shows that the actual thermodynamic noise level is lower by a factor of at least 11 than that calculated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
9
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 15 publications
1
9
0
Order By: Relevance
“…On the other hand, very recently a new model for low-frequency thermally induced length fluctuations in optical fibers was proposed by Duan (12,13), following an approach based on the fluctuation-dissipation theorem (14). A comparison with our data is already shown by Cranch and Foster (6), but a deeper analysis reveals that the expression derived from (12) is much closer to experimental findings than others.…”
supporting
confidence: 80%
“…On the other hand, very recently a new model for low-frequency thermally induced length fluctuations in optical fibers was proposed by Duan (12,13), following an approach based on the fluctuation-dissipation theorem (14). A comparison with our data is already shown by Cranch and Foster (6), but a deeper analysis reveals that the expression derived from (12) is much closer to experimental findings than others.…”
supporting
confidence: 80%
“…In fact, a thorough analysis recently reported by Skolianos et al shows that the predicted thermal noise is nearly an order of magnitude below the measured noise in [15], indicating the reported strain sensitivity may still be limited by other noises, such as the laser phase noise. Nevertheless, this debate prompts the question of whether the current technology is ready to attain thermal noise-limited fiber-optic sensing in the infrasonic range [3], [4]. The present work is an attempt by the author to address this question.…”
Section: Introductionmentioning
confidence: 98%
“…In a similar effort, Gagliardi et al demonstrated the highest strain sensitivity below 10 Hz with a fiber Fabry-Perot (FP) cavity and a frequency combstabilized diode laser [2]. However, their claim of reaching the thermal noise limit at infrasonic frequencies (below 20 Hz) has been shown to be inconsistent with theoretical predictions [3], [11], [15]. In fact, a thorough analysis recently reported by Skolianos et al shows that the predicted thermal noise is nearly an order of magnitude below the measured noise in [15], indicating the reported strain sensitivity may still be limited by other noises, such as the laser phase noise.…”
Section: Introductionmentioning
confidence: 99%
“…For the range of infrasonic frequencies (10 mHz to 30 Hz), Gagliardi et al 4 reported strain measurements with the highest sensitivity obtained by using a fiber Fabry-Perot (FP) cavity. However, the sources of the noise floor are still in doubt 18,24,25 . Recently, in the experiment for ultra-stable fiber-stabilized laser, Dong et al 8 observed that the frequency noise PSD range from 1 Hz to 100Hz exhibits a 1 f characteristic seems consistent with Duan's theory.…”
mentioning
confidence: 99%